Employee eco-initiatives and the workplace social exchange network. Issue 1 (February 2016) - Raineri, Nicolas; Mejía-Morelos, Jorge Humberto; Francoeur, Virginie; Paillé, Pascal
Abstract: The purpose of this study was to test a workplace social exchange network model of employee eco-initiatives in which high-quality relationships with the organization, the supervisor, and the coworkers, influence suggestions for constructive change toward the environment. Data were obtained from 449 university-educated Mexican employees working in the service industry. In contrast with recent research, we found that social exchanges with the organization and the supervisor were not linked to eco-initiatives, at least not directly, when controlled for social exchange with the coworkers. However, the results indicate that the quality of peer relationships mediates influences of the broader social and psychological context represented by the organization and the supervisor. These findings and their implications for theory and practice are discussed.